Innovative Learning Media: Ethnomathematics-based Modules for Third-Grade of Elementary School Students - Masruroh, Miftakhul; Amir, Mohammad Faizal (Universitas Pendidikan Ganesha, 2024)
Low learning outcomes on the properties of flat shapes for grade three elementary school students are indicated due to the unavailability of adequate modules. Meanwhile, third-grade students find it easier to learn math through cultural sites as a form of ethnomathematics. This study aims to develop an ethnomathematics-based module that is valid, practical, and effective in improving the learning outcomes of third-grade students on the material properties of flat shapes. This study uses the research and development method through the stages of analysis, design, development, implementation, and evaluation (ADDIE). The subjects of this study were 22 third-grade elementary school students. The validity of the module was measured through validator assessment using a validation questionnaire. The practicality of the module was measured using a student response questionnaire. Effectiveness was measured by comparing pre-test and post-test scores. Data collection techniques used questionnaires and tests. The validity results obtained an average value of 1 in the interval 0.80-1,00 with very valid criteria. Practicality obtained a value of 94% in the interval 85.01%-100% with very practical criteria. Effectiveness obtained a significance value of 0.000<0.05, which can improve student learning outcomes. Hence, the implication of the results of this development research is to provide a model or example of valid, practical, and effective ethnomathematics-based modules to improve the learning outcomes of third-grade students on the properties of flat shapes material.